Cezanne - Borchardt-Hume, Achim 1965-2021; Groom, Gloria 1954-; Sidlina, Natalia; Haskell, Caitlin; Muir, Kimberley; Dahm, Kristi; Verri, Giovanni; Kokkori, Maria; Granzotto, Clara (Tate, 2022)
Organized chaos: looking at Cezanne /Achim Borchardt-Hume, Gloria Groom, Caitlin Haskell and Natalia Sidlina --"At once unknown and famous": Cezanne in Paris /Gloria Groom --Cezanne's refusal /Caitlin Haskell --"A harmony parallel to nature": color, form, and space in Cezanne's watercolors and oil paintings /Kimberley Muir, Kristi Dahm, Giovanni Verri, Maria Kokkori, and Clara Granzotto --Cezanne's slow homecoming /Natalia Sidlina --Catalogue --The breakfast picnic /Lubaina Himid --When is a place /Ellen Gallagher --I paint pictures too! /Kerry James Marshall --The breaking point /Luc Tuymans --Je traîne seule /Laura Owens --The bones underneath /Rodney McMillian --Between the bathers and us, he living /Paul Chan --Then and now /Phyllida Barlow --Immaterial statements of matter /Etel Adnan --Trio /Julia Fish --Mapping Cezanne /Kathryn Kremnitzer --Contextualizing Cezanne /compiled byMichael Raymond --Cezanne in the collections of the Impressionist circle /compiled byKathryn Kremnitzer --Cezanne's materials
Diese Publikation erscheint anlässlich der gleichnamigen Ausstellung im The Art Institute of Chicago vom 15.05.2022-05.09.2022 und in den Eyal Ofer Galleries, Tate Modern, London vom 06.10.2022-12.03.2023. - Includes bibliographical references (pages 230-233) and index
Keywords: Cézanne, Paul -- 1839-1906; Cézanne, Paul; Post-impressionism (Art) / Exhibitions; Art, Modern / 19th century; Art, Modern / 20th century; Art, Modern; Post-impressionism (Art); Exhibition catalogs; Criticism, interpretation, etc; Cézanne, Paul / 1839-1906 / Exhibitions; Cézanne, Paul / 1839-1906 / Criticism and interpretation; Ausstellungskatalog -- The Art Institute of Chicago -- 15.05.2022-05.09.2022 -- Chicago; Ausstellungskatalog -- Eyal Ofer Galleries, Tate Modern -- 06.10.2022-12.03.2023 -- London; Aufsatzsammlung; Bildband